Toxicity Assay of Fermented Artocarpus altilis Leaves Using Brine Shrimp Lethality Test - Hesti Riasari; Yessi Febriani; Winda A. Nurfauziah (Universitas Padjadjaran, Indonesia)
Fermented Artocarpus altilis leaves contains phenolic compound that has pharmacological activity. Differences in fermentation method, i.e., aerobic and anaerobic fermentation might change its characteristics and biological activity. The purpose of this study was to compare toxicity properties between aerobically and anaerobically fermented Artocarpus altilis leaves using brine shrimp lethality (BSL) test. Both types of fermented leaves were cold extracted using ethanol solvent (1:6) for 3 x 24 hours. Phytochemical screening was then performed to examine the presence of secondary metabolite compounds. BSL test was performed in 7 treatment groups, i.e., negative control, 1000, 500, 100, 50, 25, 12.5 ppm of extract. Each vial contained 10 Artemia larvae, extract, and sea water up to 10 ml. Toxicity is measured by calculating LC50 after 24 hours observation. The experiment was repeated three times. The results of the study showed that LC50 of aerobic extract was 712 ppm, thus it can be categorized as toxic, while that of anaerobic extract is 1.927 ppm, or non-toxic to the Artemia salina larvae. In conclusion, aerobically fermented Artocarpus altilis leaves had toxicity potency, while anaerobically fermented Artocarpus altilis leaves had no toxicity potency against Artemia salina in BSL test. Key words: Artocarpus altilis, brine shrimp lethality test, toxicity.